Air pollution impacts due to petroleum extraction in the Norwegian Sea during the ACCESS aircraft campaign - Tuccella, P.; Thomas, Jennie; Law, K. S.; Raut, J.-C.; Marelle, Louis; Roiger, Anke; Weinzierl, Bernadett; Denier van der Gon, H. A. C.; Schlager, Hans; Onishi, Tatsuo (Elem Sci Anth, 2017)
Emissions from oil/gas extraction activities in the Arctic are already important in certain regions and may increase as global warming opens up new opportunities for industrial development. Emissions from oil/gas extraction are sources of air pollutants, but large uncertainties exist with regard to their amounts and composition. In this study, we focus on detailed investigation of emissions from oil/gas extraction in the Norwegian Sea combining measurements from the EU ACCESS aircraft campaign in July 2012 and regional chemical transport modeling.